Fish Pangek Processing Lake Singkarak In Solok Regency - Adawiyah, Nadiatul; Elida, Elida (Universitas Negeri Padang, 2024)
This research is motivated by pangek in general made from sea fish and no additional ingredients, this is different from the pangek in Nagari Paninggahan which is made from lake fish, namely bilih fish and sasaudan fish mixed with additional ingredients such as young nagka, young papaya, chayote, and sijangkang. This research was conducted with the aim of identifying the composition of ingredients, spices, tools used in making pangek in Nagari Paninggahan and explaining the processing process used in making pangek in Nagari Paninggahan.The type of research used is qualitative, the location of this research was carried out in Nagari Paninggahan, Junjung Sirih District, Solok Regency in October 2023. The data sources are Bundo Kandung and people who are experts in making pangek. Data collection techniques by conducting observations, interviews, and documentation. Data analysis in the field which includes data reduction, data presentation, conclusion drawing and verification. The results showed that pangek in Nagari Paninggahan is made from bilih fish and Sasau fish, as well as additional ingredients such as young jackfruit, young papaya, chayote and sijangkang. The spices used are red chili, shallots, garlic, ginger, galangal, lemongrass, turmeric leaves, lime leaves, bay leaves, ruku-ruku leaves, lemongrass and belimbing wuluh. The tools used are knives, plastic kom, grindstone or blender, cauldron or talenang, stove and samba plate. The process of making